2003
DOI: 10.1016/s1078-5884(03)00384-8
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy Improves Cognitive Function in Patients with Exhausted Cerebrovascular Reserve

Abstract: Attention improved at 2 months following CEA in patients with impaired CVR. CEA may offer more than reduced stroke risk to patients with impaired CVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 34 publications
6
57
1
3
Order By: Relevance
“…Reduced cerebrovascular resistance (CVR) on the side of carotid occlusion or stenosis indicates preexisting autoregulatory vasodilation and has been associated with cognitive impairment in patients with asymptomatic carotid stenosis at baseline 29 and with cognitive improvement when the impaired CVR is reversed after endarterectomy. 30 Other studies have shown a lack of association between CVR and cognitive impairment. 31 In an important single case study, cerebral hemodynamic measures were assessed in a 55-year-old man with bilateral ICA occlusions presenting with subacute onset of severe behavioral and cognitive changes.…”
Section: Resultsmentioning
confidence: 97%
“…Reduced cerebrovascular resistance (CVR) on the side of carotid occlusion or stenosis indicates preexisting autoregulatory vasodilation and has been associated with cognitive impairment in patients with asymptomatic carotid stenosis at baseline 29 and with cognitive improvement when the impaired CVR is reversed after endarterectomy. 30 Other studies have shown a lack of association between CVR and cognitive impairment. 31 In an important single case study, cerebral hemodynamic measures were assessed in a 55-year-old man with bilateral ICA occlusions presenting with subacute onset of severe behavioral and cognitive changes.…”
Section: Resultsmentioning
confidence: 97%
“…18,27,47 Overall, 16 used one or more control groups varying from healthy subjects to patients affected by different diseases. 18 Ten focused exclusively on symptomatic 5,17,21,28,33,35,43,45,27,47 and one on asymptomatic patients. 19 Time of cognitive assessment varied from 24 hours to 8 years after revascularization and 4 reported at 1 year or later (3 and 8 years).…”
Section: Search Resultsmentioning
confidence: 99%
“…To compare cognitive outcome, 12 studies used single or multiple control groups varying from healthy people (nϭ7), 19,25,29,33,34,41,42 to patients with vascular risk factors (nϭ1), 19 to those with peripheral disease (nϭ2), 20,25 those undergoing orthopedic surgery (nϭ3), 21,30,38 or those undergoing urologic surgery (nϭ1). 28 One study analyzed cognitive outcome exclusively in asymptomatic 19 and 5 in symptomatic carotid stenosis. 5,21,28,33,35 Comparing post-CEA assessment with preoperative condition with a control group, 6 reported no substantial changes after CEA, 20,23,30,33,40,42 5 highlighted impairment, 5,19,24,31,38 and 4 improvement, 21,22,35,41 although not all psychological tests were consistently changed.…”
Section: Neuropsychological Outcome After Carotid Endarterectomymentioning
confidence: 99%
“…EETs are important regulators of parenchymal blood flow and neurovascular coupling (23) and studies suggest that cognitive impairment in humans is linked to dysfunctional cerebral eicosanoid signaling (35). For comparative analysis of the effect of BCAS on arterioles and the major collateral artery between the posterior and anterior cerebral circulation, we also studied structural and mechanical changes in the PAs as well as posterior communicating arteries (PComAs) and evaluated cerebrovascular reserve capacity, a critical prognostic factor for cognitive impairment (17). The aim of this study was to evaluate changes in the PAs and collaterals such as the PComAs in a model of cognitive impairment to understand the mechanism by which cerebral perfusion and brain functions are linked.…”
mentioning
confidence: 99%